'I feel hopeless': Exploring the psychosocial impacts of caring for mentally ill relatives in Cambodia. (March 2023) - Phoeun, Bunna; Chanthorn, Leang; Schulhofer, Lena; Khann, Sareth; Soung, Thea; Conroy, Kevin; Nguyen, Amanda J.
Background: There is growing recognition of the psychosocial burden of caregiving on relative caregivers of the mentally ill in low-and middle-income countries. Yet there remains limited formal research examining the challenges and psychosocial support needs of these relative caregivers, particularly with sensitivity to understanding caregiver experiences across diverse cultures and contexts. The purpose of this study was to study caregiver burden to inform potential intervention approaches among relative caregivers of treatment-engaged mentally ill patients in Cambodia. Methods: Participants were all relative caregivers identified through their connection to a non-governmental organization providing psychiatric care. Five focus group discussions were held with 37 participants to explore challenges experienced by relative caregivers. A total of 115 caregivers then completed a mental health assessment consisting of the Patient Health Questionnaire – 9 item scale, Generalized Anxiety Disorder – 7-item scale, and 21-item Depression, Anxiety, and Stress Scale. Internal consistencies ranged from α = .81 to .87 across scales. Results: Five themes emerged from the focus group discussions: financial burden, erratic behavior of patients, social alienation, somatic and emotional symptoms, and barriers to help-seeking. Assessment data indicated the sample was highly symptomatic. Women and those with no employment appeared to be at higher risk of distress, as were those caregivers with a biological relationship to the patient (parents, children, and siblings; relative to spouses or other relationships). Discussion: Findings suggest a need for regular screening and greater psychosocial support for relative caregivers. It is notable that the needs identified within the current study remain prominent even as this is a treatment-engaged sample.